2010
DOI: 10.1073/pnas.0910359107
|View full text |Cite
|
Sign up to set email alerts
|

T and B cell hyperactivity and autoimmunity associated with niche-specific defects in apoptotic body clearance in TIM-4-deficient mice

Abstract: TIM-4, a member of the TIM family expressed on antigen-presenting cells, binds to phosphatidylserine exposed on the surface of apoptotic bodies. However, the significance of this interaction in vivo remains unknown because other receptors have been implicated in the clearance of apoptotic bodies and could compensate for the TIM-4 deficiency in vivo. In this study, we describe the generation of TIM-4-deficient mice and address whether TIM-4 serves a unique function in vivo. We show that TIM-4 −/− peritoneal mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
179
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(195 citation statements)
references
References 25 publications
(45 reference statements)
7
179
0
5
Order By: Relevance
“…purposes of phagocytic removal (15,16,(20)(21)(22). The crystal structure of Tim4 in complex with a single-PS head group has provided invaluable insight into how Tim4 specifically recognizes a single-PS molecule (23).…”
mentioning
confidence: 99%
“…purposes of phagocytic removal (15,16,(20)(21)(22). The crystal structure of Tim4 in complex with a single-PS head group has provided invaluable insight into how Tim4 specifically recognizes a single-PS molecule (23).…”
mentioning
confidence: 99%
“…Another obstacle to the application of anti-TIMs mAbs is the possibility of inducing adverse toxicity, most commonly reversible autoimmunity or systemic inflammatory reactions. 52,61 In conclusion, TIM molecules play critical roles in the regulation of tumor immunosurveillance and anti-tumor immunity, and anti-TIMs mAbs can be utilized as potent tools to manipulate the functions of various immune cells, and thus orchestrate immune responses against tumors. The molecules have the potential to greatly impact the therapeutic effects of cancer regimens.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TIM-4 serves as a critical phagocytosis receptor in peritoneal macrophages, since the deficiency of TIM-4 results in a significant decrease in the ability of peritoneal macrophages to engulf apoptotic cells. 61 However, splenic and tumor-associated macrophages were still able to engulf apoptotic cells even in the absence of TIM-4, suggesting the existence of other phagocytosis receptors expressed in these subsets of APCs. 61,62 Recent studies have identified a novel role of TIM-4 in the regulation of tumor immunity and antitumor immune responses.…”
Section: Tim-4mentioning
confidence: 99%
See 1 more Smart Citation
“…55 (d) TIM-4 expression is largely restricted to APCs, and it serves as a phosphatidylserine receptor that regulates the engulfment of apoptotic cells; it interacts with TIM-1 on T cells to regulate the differentiation of Th1 and Th17 cells. 34,57,59 APC, antigen-presenting cell; DAMP, damage-associated molecular pattern; DC, dendritic cell; NK, natural killer; Sema4A, Semaphorin 4A; TIM, T-cell immunoglobulin mucin. acids into DC endosomes, which blocks innate immune signaling pathways upstream of PRR-sensing systems.…”
Section: Tim-3mentioning
confidence: 99%